THE ROLE OF COMPLEX SENTENCES IN THE ARTISTIC STYLE OF ERNEST HEMINWAY AND SAID AHMAD (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article presents a comparative analysis of the stylistic functions of complex sentences in the prose of E. Hemingway and Said Ahmad. The research is based on Hemingway’s The Old Man and the Sea, A Farewell to Arms, For Whom the Bell Tolls and Said Ahmad’s Ufq, Jimjitlik, Qo’shchinor chiroqlari. Five principal stylistic features of Hemingway’s complex sentence usage (la-conic subordination, rhythmic contrast, dramatic tension, character revelation, subtext) and five char-acteristic features of Said Ahmad’s usage (multi-layered description, emotional intensification, folk rhythm, philosophical generalization, lyrical digression) have been identified. For the first time, the “Grammatical Complexity Index” (GCI) formula is developed and applied to the works of both writers. GCI results show that Hemingway’s average GCI is 1.18, while Said Ahmad’s is 1.72. Hemingway’s “semantic condensation” and Said Ahmad’s “descriptive expansion” strategies are scientifically sub-stantiated. A Lexical Diversity Index (LDI) analysis within complex sentences is also conducted: Hemingway 0.64, Said Ahmad 0.81.
Keywords: Complex sentence, stylistic function, literary style, comparative analysis, E. Hemingway, Said Ahmad, Grammatical Complexity Index, semantic condensation, descriptive expansion, subor-dination, linguostylistics.